-7z-10=10+3z

Simple and best practice solution for -7z-10=10+3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7z-10=10+3z equation:



-7z-10=10+3z
We move all terms to the left:
-7z-10-(10+3z)=0
We add all the numbers together, and all the variables
-7z-(3z+10)-10=0
We get rid of parentheses
-7z-3z-10-10=0
We add all the numbers together, and all the variables
-10z-20=0
We move all terms containing z to the left, all other terms to the right
-10z=20
z=20/-10
z=-2

You can always share this solution

See similar equations:

| -r+10=9r-10 | | 9.78+3.5u=-9.11+0.6u-0.25 | | 2x-(3x-8)=2 | | 8x^2-30x+45=0 | | 8x(2-30x+45=0 | | 7(6x=54) | | 8h+1=10+9h | | Q=1/2p+3 | | 7c+2+10c=-10c+2 | | 2x/2.8=8.2 | | 2t+10=4t-8 | | -10y+9=-7y-5y+9 | | -m+3=m-7 | | 3x+12=3x+25 | | 4x^-3+1=0 | | 6.4g+4=3.4g+10 | | -10d-1+3D=-d-1 | | 2.8/x=35 | | 8+f=-5f-10 | | 8-5h=-9h | | 5+8=18(3?x)?5+8=18 | | 3x+2(-12)=64 | | -4.1=8.7+y/8 | | 4x+14=5x+4=6x-3 | | -4.1=8.7=y/8 | | 2l+8=12 | | 77-3a=44 | | 2.7x=1.62 | | 5+19x?7?26x=?51 | | 5x+-10=3x+30 | | y+2(2.5)=15 | | 12(x-0,5)=4x-34 |

Equations solver categories